2023
DOI: 10.1186/s12889-023-15992-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B vaccination coverage and associated factors among medical students: a cross-sectional study in Bosaso, Somalia, 2021

Abstract: Background Hepatitis B virus (HBV) is a leading cause of liver cancer and remains a global public health concern. The risk of acquiring HBV is higher in HCWs than in non-HCWs. Medical students are considered a high-risk group because similar to HCWs, they tend to be exposed to body fluids and blood during training in clinical settings. New infections can be effectively prevented and eliminated with an increased coverage of HBV vaccination. The purpose of this study was to evaluate HBV immunizat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
(40 reference statements)
1
4
1
Order By: Relevance
“…It is also consistent with findings from another study by Issa et al [ and 10.9% in Burkina Faso by Ouédraogo et al [37]. This brings to the fore, the generally low vaccination coverage in Ghana and African at large [38,39]. The observed complete vaccination coverage in this study is lower compared to what has been found in a study by Yuan et al (60%) in China [40] and Guthmann et al (91.7%) in France [41].…”
Section: Discussionsupporting
confidence: 92%
“…It is also consistent with findings from another study by Issa et al [ and 10.9% in Burkina Faso by Ouédraogo et al [37]. This brings to the fore, the generally low vaccination coverage in Ghana and African at large [38,39]. The observed complete vaccination coverage in this study is lower compared to what has been found in a study by Yuan et al (60%) in China [40] and Guthmann et al (91.7%) in France [41].…”
Section: Discussionsupporting
confidence: 92%
“…Improvement Strategies: Participants in the study proposed improvement strategies that emphasize raising awareness, supporting primary healthcare centers, and increasing funding allocation for HBV control efforts. These strategies align with global health frameworks such as the Sustainable Development Goals and stress the importance of policy interventions, mandatory vaccination policies, and the regulation of risky practices [24,25,26] .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in the study area, limited availability, and high costs of the vaccine act as barriers to achieving national HB vaccination coverage, thereby increasing the risk of infection. A separate study assessing HB vaccination coverage among Somali people found that 2.8%, 16.0%, and 33.4% of healthcare workers and medical students were not fully HB vaccinated and cited vaccine unavailability and high vaccine costs as reasons for not getting vaccinated [ 60 – 62 ]. This study underscores the importance of improving vaccine uptake by addressing issues related to vaccine availability and reducing associated costs.…”
Section: Discussionmentioning
confidence: 99%